Does going cashless make you tax-rich? Evidence from India's demonetization experiment - Satadru Das; Lucie Gadenne; Tushar K. Nandi; Ross Warwick (Institute for Fiscal Studies (IFS), 2022)
This paper investigates the effect of electronic payments technology on firms' tax compliance in a large developing economy. We consider India's demonetization policy which, by limiting the availability of cash, led to a large increase in the use of electronic forms of payments. Using administrative data on firms' tax returns and variation in the strength of the demonetization shock across local areas, we find that greater use of electronic payments leads to firms reporting more sales to the tax authorities. This effect is strong enough to explain roughly half of the large (11%) increase in reported sales observed during demonetization.
Keywords: H26; O23; H25; 330; tax compliance; electronic payments; demonetization